Drug therapeutic failures as a cause of admission to an intensive care unit at a university hospital - Jair Antonio Ruiz-Garzon; Camilo Andrés Rojas-Velandia; Carlos-Alberto Ca (Wolters Kluwer Medknow Publications, 2019)
Objective: Drug therapeutic failures (TFs) are included in pharmacovigilance reporting, as some authors consider them a type of adverse drug reaction. Given their high frequency in Colombia, we studied their importance as a cause of admission to an intensive care unit (ICU). Methods: This was a cross-sectional observational study. Clinical records of patients who arrived at the emergency service of a third-care level university hospital were reviewed. Information was collected by a resident in clinical toxicology, and each case was validated and analyzed by a research team using the algorithm proposed by Vaca González and Schumock and Thornton criteria for preventability to evaluate the existence of possible medication errors. Findings: In total, 697 clinical records were evaluated and 18 patients presented TFs (2.6%, 95% confidence interval 1.5%-4.1%) as the cause of admission to the ICU. The most frequent TFs were seizures (56%) and hypertension (28%). The most commonly associated medications were valproic acid (28%) and losartan (28%). Ten cases (56%) were associated with drug misuse and the same number of cases was preventable, according to Schumock and Thornton criteria. Conclusion: This is the first study assessing TFs as a cause of admission to the ICU in the Colombian population. The frequency of TFs in our study was similar to that described in the literature; being the most common cause the inappropriate drug use, particularly for drugs with complex kinetics, such as antiepileptic drugs.